2017
DOI: 10.3390/su9091544
|View full text |Cite
|
Sign up to set email alerts
|

Overheating and Daylighting; Assessment Tool in Early Design of London’s High-Rise Residential Buildings

Abstract: High-rise residential buildings in dense cities, such as London, are a common response to housing shortage. The apartments in these buildings may experience different levels of thermal and visual comfort, depending on their orientation and floor level. This paper aims to develop simplified tools to predict internal temperatures and daylighting levels, and propose a tool to quickly assess overheating risk and daylight performance in London's high-rise residential buildings. Single-and double-sided apartments in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…As our study cities are located in warm or mild temperate climactic zones, where summers can exceed the human comfort range ( Australian Bureau of Statistics, 2013 , p. 4671), it is unsurprising that requirements intended to increase daylight to apartments negatively impacted summer thermal comfort. However, this is not only a challenge for hotter climates – a study of high-rise apartments in London found that the attributes that increased sunlight exposure (i.e., orientation, higher floor level, high glazing ratios) exceeded sunlight requirements and increased vulnerability to overheating in summer ( Nebia & Tabet Aoul, 2017 ). This embodies the challenge of designing apartments that promote access to sunlight and thermal comfort in both summer and winter, as the design requirements intended to improve sunlight access undermined summer thermal comfort but promoted winter thermal comfort.…”
Section: Discussionmentioning
confidence: 99%
“…As our study cities are located in warm or mild temperate climactic zones, where summers can exceed the human comfort range ( Australian Bureau of Statistics, 2013 , p. 4671), it is unsurprising that requirements intended to increase daylight to apartments negatively impacted summer thermal comfort. However, this is not only a challenge for hotter climates – a study of high-rise apartments in London found that the attributes that increased sunlight exposure (i.e., orientation, higher floor level, high glazing ratios) exceeded sunlight requirements and increased vulnerability to overheating in summer ( Nebia & Tabet Aoul, 2017 ). This embodies the challenge of designing apartments that promote access to sunlight and thermal comfort in both summer and winter, as the design requirements intended to improve sunlight access undermined summer thermal comfort but promoted winter thermal comfort.…”
Section: Discussionmentioning
confidence: 99%
“…For example, excessive internal heat caused by highly insulated and airtight structures without appropriate passive cooling strategies caused thermal discomfort of residents, as confirmed, e.g., by Badescu et al [5] and Shrubsole et al [6]. Overheating of the top stories of buildings frequently occurred [7][8][9]. During the summer season peak, ambient temperatures occasionally prohibit sufficient free cooling and require the use of mechanical cooling systems in very well-insulated buildings.…”
Section: Introductionmentioning
confidence: 93%
“…The use of this software in energy simulation is gaining attention within research framework. Indeed, it has been used in several studies to assess, for instance, the energy consumption of a market building in New Taipei [38], the energy saving potential of an air handling unit within an office building in Singapore [39], the overheating risks and daylighting levels in high-rise residential buildings placed in London [40], and also the building energy demand at community level [41].…”
Section: Implementation Of the Energy Modelmentioning
confidence: 99%